2020
DOI: 10.1093/cid/ciaa149
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Detection of 2019 Novel Coronavirus in Saliva

Abstract: The 2019 novel coronavirus (2019-nCoV) was detected in the self-collected saliva of 91.7% (11/12) of patients. Serial saliva viral load monitoring generally showed a declining trend. Live virus was detected in saliva by viral culture. Saliva is a promising noninvasive specimen for diagnosis, monitoring, and infection control in patients with 2019-nCoV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
1,683
6
78

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,691 publications
(1,868 citation statements)
references
References 11 publications
34
1,683
6
78
Order By: Relevance
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%
“…Since archived specimens were used, written informed consent was waived. 12 of 23 patients included in this study have been reported previously, 6 but their clinical information, viral load by single copy RNA-dependent RNA polymerasehelicase gene, antibody response, or viral genome analysis has not been reported before.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The false negative rate of oropharyngeal swabs seems high. As we know that, oropharyngeal swabs are the recommended upper respiratory tract specimen types for SARS-CoV-2 diagnostic testing7,8 , so a new detection technique should be developed as soon as possible.…”
mentioning
confidence: 99%